An educational intervention for medical students to improve self-efficacy in firearm injury prevention counseling - Jacky Z. Kwong; Jennifer M. Gray; Lisa Rein; Ying Liu; Marlene D. Melzer-Lange (BMC, 2019)
Abstract Background Most physicians support counseling patients about firearm injury prevention (FIP), but infrequently do so due to lack of training and low confidence. Interventions to increase counseling frequency should focus on improving physician self-efficacy. Firearm injuries affect many clinical specialties; therefore, trainees would benefit from early FIP education. This study aims to determine if a 20-min educational intervention improves self-efficacy in FIP counseling in third-year medical students. Knowledge and beliefs were also assessed as secondary indicators of self-efficacy. Methods This was a prospective study performed at a medical school associated with a tertiary care children's hospital during the 2016-17 academic year. Groups of 12-15 different third-year medical students were selected to receive either a 20-min intervention or control lecture during their monthly pediatric lectures. The intervention consisted of two clinical vignettes, a brief discussion about the importance of FIP, and suggestions for clinical integration. The control session was a case-based lecture about pediatric emergencies. Participants completed baseline electronic assessments. Intervention students also completed post-intervention assessments immediately following each session. All participants completed final assessments at 6 months. Data were analyzed using Wilcoxon signed-rank tests and Wilcoxon rank-sum. Results We surveyed a total of 130 students. Sixty-five students completed the entire series of assessments - 22 from the control and 43 from the intervention group. There were no significant differences between the control and intervention groups at baseline. Immediately after, intervention, participants reported feeling more self-efficacious, had improved knowledge of FIP risk factors, and had beliefs more consistent with providing FIP anticipatory guidance (p <  0.001 for all three measures). After 6 months, participants sustained improvement in one of two self-efficacy questions ("I feel ready to counsel patients about firearm injury prevention") and retained knowledge of risk factors (p <  0.05 for both). However, their beliefs did not significantly favor FIP counseling, and they were not more likely to engage in a conversation about firearm safety. Conclusions A 20-min educational intervention acutely improved self-efficacy in FIP counseling in third-year medical students, but improvements weakened after six months. Without further training, the beneficial effects of a one-time intervention will likely wane with time.